الحماية القانونية لحقوق الطفل في العالم العربي "نحو وضع تشريع نموذجي لحقوق الطفل - مستاري, عادل (Revue jurisprudence, 2018)
الحماية القانونية لحقوق الطفل في العالم العربي "نحو وضع تشريع نموذجي لحقوق الطفل